(untitled) (Journal of Pharmaceutical Negative Results, 2022)
Annotation: The article presents the results of a study of the crossing ability of cotton varieties in terms of yield in 2019-2021. At thesame time, on average, high yields were observed in the varieties "Sultan", "S-7300", "Ilgar" from maternal forms, as well as"UzPITI-202", "Andijan-36", "UzPITI-201" varieties from paternal forms. The efficiency of general crossability (OCS) was notedamong the maternal forms in the varieties "Sultan" and "Ilgar", and among the paternal forms in the variety "UzPITI-202".In other varieties, the efficiency of ACS is unstable over the years, showing an inefficient indicator based on the average annualindicator.In terms of productivity, it was found that the overall crossability of the varieties "Sultan", "Ilgar" and "UzPITI-202" is high.Thesevarieties are recommended as primary material for cotton breeding.